A review of Chinese medicine for the treatment of psoriasis: principles, methods and analysis - Yang Su; Wen Qin; Lun Wu; Bingyou Yang; Qiuhong Wang; Haixue Kuang; Genhong Cheng (BMC, 2021)
Abstract Chinese medicine (CM) has a long history in the treatment of psoriasis, and its different understanding angle and treatment mode from modern medicine have unique wisdom. In this article, we consulted a large number of literatures and collected data in order to systematically clarify how CM understands psoriasis, including the classification and judgment of syndrome types, the diagnosis and thinking of etiology and pathogenesis, the application of treatment ideas, principles, methods and various prescriptions, and suggestions on patient care, so as to provide a clear CM treatment process and experience for the world clinic. In addition, we analyzed the efficacy and safety through clinical data, and summarize the methods and prescriptions worthy of promotion, so as to provide reference for doctors to prescribe prescriptions and medication. Finally, we found that compared with modern medicine, CM has unique advantages in the treatment of psoriasis, including the uniqueness of syndrome classification, the abundantly and flexibility of treatment ideas. Not only many famous doctors have studied the ideas in ancient books, but also made great efforts to innovate, which has left a lot of valuable experiences for clinical practice. Moreover, a large number of treatment methods, prescriptions and medicines have achieved high effectiveness and safety in clinical practices for many years, which has been proved to be worthy of clinical reference and in-depth research. In addition, we also think about the deficiencies of CM in the treatment of psoriasis and the direction of breakthrough combined with modern medicine. The treatment of psoriasis with CM is worth popularizing, and we hope it can benefit more patients.